Genome and karyotype differences between diploid and tetraploid desert roses - Rosa, Talita Angélica de Oliveira; Silva, Juliana Machado da; Valentim, Thamirys Silva; Assis, Rafael de; Parteka, Letícia Maria; Vanzela, André Luís Laforga (Ornamental Horticulture, 2025)
Adenium (Apocynaceae) is a genus that contains succulent species, with sculptural stems and large variations in flower shapes and colors. Most of the world's production chain consists of hybrids, and A. obesum (2n = 22) is the species with the greatest ornamental interest. Adenium arabicum (2n = 44) and A. obesum differ in their morphological characteristics and are found in distinct geographical areas. However, according to botanical nomenclature rules, A. arabicum should be named A. obesum or a variety thereof. Although genetic variation data for desert roses is scarce, it is crucial for the ornamental plant production sector. The objective of this study was to gain an understanding of the genomic diversity among diploid and tetraploid A. obesum varieties through the use of various cytomolecular methods. The karyotypes were composed of meta- and submetacentric chromosomes, and the genome size ranged from 2C = 1.98 pg in diploid samples to 2C = 2.92 pg in tetraploid samples. Chromosome banding revealed similarities between the varieties, with the accumulation of AT-rich regions (DAPI+) bands present in the proximal-interstitial chromosome regions, and a smaller amount of GC-rich regions (CMA+). The DAPI+ and CMA+ regions, along with ribosomal DNA and Gypsy retrotransposons, predominated in the interphase chromocenters. Differences in the morphology, chromosome number, in situ hybridization signals, and the DNA C-value decrease between these two groups of samples reinforces that they are distinct species and not varieties. Such information is important for the genetic improvement of desert roses.